An Analysis of Learner Errors in Written Production Made By The Students of SMA Negeri Colomadu - Sugiyono, Sugiyono (2011)
Learning English becomes more and more important nowadays since we know that English is one of the International Language which can be used to communicate around the world. In Indonesia, English is learnt as a foreign language. Learning a different language is sometimes difficult since the target language has different element compared to the source language. These differences sometimes cause students to make errors when using it. The present study deals with English used by the researcher of written production made by The Senior High School students of SMA Negeri Colomadu Karanganyar. It is worth studying because of the phenomenon that their English is marked with a significant number of errors. This phenomenon has encouraged me to carry out a study on errors analysis in order to find proof or evidence that their English is still at the level language learner. In conducting this study at least there are three major stages which have been done, namely; recognition, description and explanation of errors. In order to make the study more comprehensive, I have also discussed things that can be implied from the findings of this research. The study examines sentences containing errors from the written production made by 15 students. The students consist of 8 males and 7 females. I have collected approximately 270 sentences containing different types of errors. All of the errors in written production are classified into 11 categories. The 11 categories are divided into 62 types of errors. These sentences are then used as the data of this study. The result of the study shows that the eleven categories of errors committed by the students are prepositions, verbs, articles, TO BE, , conjunction, bound morpheme, adjective, pronouns, vocabulary, grammatical construction and miscellaneous errors In order to have clear description of the degree of interference from the first as well as from the target language, the errors are classified based on the surface strategy taxonomy, comparative taxonomy and communicative effect taxonomy. In surface strategy taxonomy, there are omission, addition and misorering. In comparative taxonomy, there are developmental errors and interlingual errors. Communicative effect taxonomy, there are global errors and local errors. Next, all types of errors are calculated. This calculation is aimed at finding out the total number of errors as well as the frequency of each types of errors. The highest percentage of errors is recorded for verbs (21.85%) and the lowest percentage is recorded for errors categorized as pronoun and miscellaneous errors (1.85%). The conclusion that can be drawn from this study is that there are several types of errors that are done in written production made by the students of SMAN Colomadu Karanganyar. Based on the result of the data analysis, the researcher find the dominant types of errors are verbs (21.85%), preposition (16.67%), bound morpheme (16.29%) and TO BE (15.56%). It means that the students still have difficulties in this area. There are some possibilities causes of errors. The students are lack of understanding the tenses. In teaching learning process, the teachers only focus on reading section. The other possible causes of errors in verbs, the students don't understand the verbs when they make sentences. They have limited knowledge of verbs. In Indonesia, we will never find TO BE, V-O, V-1, V-2, V-3 or verb forms.